The large‐scale frozen‐in anticyclone in the 2011 Arctic summer stratosphere. Issue 6 (22nd March 2013) - Allen, Douglas R.; Douglass, Anne R.; Strahan, Susan E.
Abstract : [1] The 2011 Arctic stratospheric final warming was characterized by a large‐scale frozen‐in anticyclone (FrIAC) that rapidly displaced the winter polar vortex, establishing unusually strong polar easterlies. A comprehensive overview of the 2011 FrIAC is provided using meteorological analyses, Microwave Limb Sounder (MLS) N2 O observations, and N2 O simulations from the Global Modeling Initiative (GMI) 3‐D chemistry and transport model and the Van Leer Icosahedral Triangular Advection (VITA) 2‐D (latitude × longitude) isentropic transport model. A vortex edge diagnostic is used to determine the FrIAC boundary, allowing quantification of several FrIAC properties. The 2011 FrIAC originated over North Africa in late March and traveled eastward and poleward over 2 weeks, forming a strong anticyclone that extended from 580–2100 K potential temperature ( 25–50 km). Low potential vorticity (PV) was transported to the pole with the FrIAC in early April; during May, most of the PV signature decayed due to diabatic processes. A small remnant negative PV anomaly persisted near the pole until mid‐June. Tracer equivalent latitude was low initially and remained low throughout the summer. GMI, VITA, and MLS showed elevated N2 O in the FrIAC, although the peak value was smaller in GMI due to a subtropical low bias. The high‐resolution ( 20 km) VITA filamentary structure quantitatively matched most of the features observed by MLS when smoothed to match the MLS resolution. The high‐N2 O anomaly persisted in the middle stratosphere over 4 months until late August, when it was destroyed by horizontal and vertical shearing, combined with photochemical processes. Key Points: A large‐scale frozen‐in anticyclone (FrIAC) occurred in 2011 Characteristics of the FrIAC examined using vortex edge algorithm Model simulations of N2 O in FrIAC reveal transport processes